Klasifikasi Status Gizi Orang Dewasa Menggunakan Algoritma Naïve Bayes (Studi Kasus Klinik Bhakti Mulia Cikarang) - Wahyu Hadikristanto1; Tiara Deswara Pungkas (Teknik Informatika, Universitas Pelita Bangsa, 2019)
Nutritional status is a condition caused by a balance between nutrient intake from food and nutritional needs by the body. The nutritional status of adults is sometimes less stable and there are many irregular eating patterns. To find out the nutritional status of adults, research on nutritional status in adults is carried out. Therefore, this study was made with a naïve bayes algorithm to determine the nutritional status of adults. Naïve Bayes is a simple probability-based prediction technique that is based on the application of the Bayes theorem, and the end result will be seen from the most appropriate or accurate value, so that this algorithm is considered to be good enough in performing probabilities to determine results. In this study, a naïve bayes algorithm was used to determine the nutritional status of adults. Data are classified into three, namely Normal, Less, and Obesity. This trial was conducted with 150 data, and the results of the accuracy obtained were 88.67%. Keyword : Nutritional Status, Classification, Data Mining, Naïve Bayes Algorithm